In between frames 24 Oras and Newsbreak framing of news on peace and conflict in Mindanao - Abellano, Gladys Mae T.; Solis, Randy Jay C. (2012)
"The long-standing GRP-MILF conflict in Mindanao has exacted a great toll on the country, with hundreds of dead Filipinos, millions of Filipinos displaced and millions worth of properties damaged; not to mention the emotional and cultural trauma inflicted, Many studies have proven the extensive influence of media over what and how people think. Logically, media would also have an effect on how Filipinos think about the Moro conflict in Mindanao. With such a heavy responsibility on its shoulders do media fulfill their role as the watchdog press,or are they bound by their own vested interests? This stud sought to better understand the framing process, including the influences on framing and the difference in the resultant frames, involved in the reportage of the Moro conflict in Mindanao by reporters from both public and privately owned broadcast networks, NBN and GMA Network. The study utilised an integrated framework based on De Vreese's Integrated Process Model of Framing, Shoemaker and Reese's Hierarchical Model of Influences on Media Content and Galtung's Peace Journalism and War Journalism Frames. Research was carried out through content analyses on Moro conflict news stories in 2011 from both networks, and focused interviews with 2 journalists each from NBN and GMA Network. The data obtained was then analysed under the lens of media ownership. Results showed that 24 Oras favored the war journalism frame, and that they more often than not sensationalized news regarding the GRP-MILF conflict in Mindanao, NBN was found to favor the peace journalism frame, and tended to concentrate solely on government generated and government related news, acting as a "sounding board" for the government. The most influential factors on news framing for all reporters were their professional stance and journalistic responsibilities as reporters, and their respective organizations. From the study's results, there is an evident need for both networks to compromise if they are to fulfill there duties to society as the Fourth Estate. GMA needs to unbend and take the initiative to educated and enlighten Filipinos about the Moro conflict in Mindanao; while NBN needs to put more effort into engaging the public instead of just providing news and information about the peace process and other government initiatives pertaining to the Moro conflict in Mindanao."
Vita.
Undergraduate thesis (A.B. Communication Research)--University of the Philippines, Diliman.
Keywords: Muslim -- Christian conflicts -- Press coverage; Muslims -- Philippines -- Social conditions